Superman returns [videorecording (DVD)] - Singer, Bryan, 1965-; Adler, Gilbert, 1946-; Peters, Jon; Dougherty, Michael; Harris, Dan, 1979-; Routh, Brandon; Bosworth, Kate, 1983-; Spacey, Kevin; Marsden, James, 1973-; Posey, Parker, 1968-; Langella, Frank; Huntington, Sam, 1982-; et al. (Superman 5-film collection, 2006)
Following a mysterious absence of several years, the man of Steel returns to Earth. While archenemy Lex Luthor plots to render him powerless once and for all, Superman faces the realization that Lois Lane has moved on with her life.